Latitudinal diversity patterns of diatoms in the Southwestern Atlantic and Antarctic waters - Olguin Salinas, Hector (2015)
Latitudinal changes in the species richness of planktonic diatoms in Southwestern Atlantic and Antarctic waters (29-76 S) were analyzed from local to regional scale in three spring and one summer seasons. A total of 220 diatom species (16-87 per station) were recorded. Despite the noticeable interannual variability, species richness showed a maximum in the northern sector of the Brazil-Malvinas Confluence Zone and a highly significant decrease with latitude.